Clinical Evaluation of Violet Light Filtration and High-Resolution Lathing on a Diffractive Extended Depth of Focus IOL - Daniel H. Chang; Andrew A. Kao; Laura K. Huggins; Jacqueline N. Albert; Jacqueline N. Whinery; Brittany M. Camirand (Ophthalmology and Therapy)
Abstract Introduction This study is a prospective, randomized, subject/evaluator-masked clinical trial in a single-center clinical setting. The purpose of the study is to compare the clinical performance of Tecnis Symfony Optiblue IOL (models ZXR00V and ZXW150) with violet light filter (VLF) and manufacturing improvements versus Tecnis Symfony IOL (models ZXR00 and ZXT150) with ultraviolet light filter (UVF) in patients undergoing cataract surgery. Methods Patients with cataracts aged ≥ 22 years were randomly assigned 1:1 to bilateral implantation with ZXR00V/ZXW150 (VLF group) or ZXR00/ZXT150 (UVF group). Key endpoints at 6 months postoperative included patient reported nighttime dysphotopsia symptoms, 25% low contrast visual acuity with glare, and patient satisfaction. Results Sixty patients were implanted with ZXR00V/ZXW150 (30) or ZXR00/ZXT150 (30). At 6 months, the VLF group did not show a statistically significant differences in mean monocular photopic uncorrected distance visual acuity (UCDVA), best-corrected distance visual acuity (BCDVA), uncorrected near visual acuity (UCNVA) (40 cm), or distance-corrected near visual acuity (DCNVA) (40 cm) compared to the UVF group. At 1 month, patients in the VLF group reported significantly less difficulty due to halo (p = 0.016) and starburst (p = 0.028) symptoms. By the 6 months, dysphotopsia complaints were no longer significantly different between the groups. Although the VLF group trended toward better low contrast visual acuity and patient satisfaction, statistical significance was not reached. Conclusions Managing the patients’ expectations is key to achieving success. At the 1-month visit the patients who reported dysphotopsia complaints in the VLF group had significantly less difficulty with starbursts and halos as compared to the UVF group. By the 6-month visit, there was no significant difference between the two groups in the difficulty with starbursts and halos. Trial Registration ClinicalTrials.gov identifier, NCT06567834.